LAJU PERTUMBUHAN POPULASI IKAN GETE-GETE BESAR (Glossamia wichmanni) DI PERAIRAN DANAU SENTANI [Growth Rate Population of Glossamia mchmanni in Sentani Lake] - Hendra Satria; Ronny Syam (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2007)
Research on population dynamics aspect of Glossamia wichmanni was conducted in January until November of 2006. Length frequency data analysis was done to estimate the growth parameter and fish population parameter with program package FiSAT. The research result of fish growth population was formulated according to Von Bertalanffy Growth Formula as Lt = 30.1 (1 - e ' 1(1 *0 1588)). recruitment pattern of fish stock showed a single of top recruitment, whereas the level exploitation stock fish in this time was E = 0.2896. The level exploitation value was still under the level of maximum exploitation (E = 0.468). Though mount the exploitation stock the fish still lower but management of original fish types potency in adjacent of Sentani lake waters shall be done to make sustainable yield by specifying fishery zones, make conservation area as specially indigenous species, lesser or negate all human activities be able to depressing of the original fish population be likely existence of introduction exotics fish types that were by introduction or not on purpose.